2019
DOI: 10.1002/ece3.5787
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic structure and formation mechanism of shrub communities in arid and semiarid areas of the Mongolian Plateau

Abstract: The mechanisms of species coexistence within a community have always been the focus in ecological research. Community phylogenetic structure reflects the relationship of historical processes, regional environments, and interactions between species, and studying it is imperative to understand the formation and maintenance mechanisms of community composition and biodiversity. We studied the phylogenetic structure of the shrub communities in arid and semiarid areas of the Mongolian Plateau. First, the phylogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 64 publications
(102 reference statements)
3
11
0
Order By: Relevance
“…This finding supports the idea that the functional structure should be better linked with local and contemporary drivers because the functional traits are more plastic compared with the phylogenetic relations, which are mainly shaped by historical and regional processes (Feng et al, 2014;Li et al, 2019). A recent study about shrub communities in this region also suggests that compared with the leaf width and leaf length, the height shows a low phylogenetic signal and high plasticity (Zheng et al, 2019).…”
Section: Soil Nitrogen Content and Community Structuresupporting
confidence: 78%
“…This finding supports the idea that the functional structure should be better linked with local and contemporary drivers because the functional traits are more plastic compared with the phylogenetic relations, which are mainly shaped by historical and regional processes (Feng et al, 2014;Li et al, 2019). A recent study about shrub communities in this region also suggests that compared with the leaf width and leaf length, the height shows a low phylogenetic signal and high plasticity (Zheng et al, 2019).…”
Section: Soil Nitrogen Content and Community Structuresupporting
confidence: 78%
“…However, the decline in sheep health and meat quality caused by seasonal nutritional deficiencies has always been the main problem in the production of naturally grazing sheep [ 3 ]. Mongolian Plateau is a typical arid and semiarid region, with mean annual precipitation varying between 40-450 mm and 80-90% of the precipitation falling between June and September, decreasing from the southeast toward the northwest [ 4 ]. The mean annual temperature ranges between -2 and 6°C and has a frost-free season of 70-160 days [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…If competitive exclusion arises from competition among species, then the phylogenetic assembly of a community will be overdivergent [6]. In contrast to niche theory, Hubbell's neutral theory is based on a stochastic process; it holds that equal niches exist among different species, and the number of coexisting species is constrained by random processes and spatial distance [7,8]. Researchers have found that evergreen broad-leaved forests show phylogenetically random structures [9].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have used a phylogenetic approach to investigate the predominant processes that underlie community structure [6,8,9,11]. Community phylogenetic structure is mainly reflected in two aspects: one is that measure the relatedness of species occurring together in a community or sample, and the other is that measure the concordance of phylogenetic and ecological dissimilarities among species [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation